Content analysis of hotel guest comment cards - Marković, Suzana (Naše gospodarstvo, 2010)
If properly designed, administered, and analysed, the process of monitoring customer satisfaction and service quality can be beneficial to any hotel firm and make all the difference between offering a mediocre service and one of exceptionally high quality. The purpose of this study is to examine hotel guest comment cards (GCCs) and customer satisfaction management schemes in Opatija's hotels. This study adopts the applied content analysis approach (Gilbert and Horsnell 1998), comparing and recording findings based on a set of best practice criteria.
Keywords: Croatia; Hrvaška; hoteli; hotelirstvo; storitve; kvaliteta; zadovoljstvo; merjenje